Política de Gestão de Estoque para Centro de Distribuição de Medicamentos. - Gama, Adonai Ferreira (Universidade Federal do Tocantins, 2022)
The present work aims to develop a study on some aspects related to the medicine and hospital material storage policy, which aims to ensure the quality and safe storage of medicines at the distribution center. It consists of a set of procedures involving receipt, storage/guarding, security against physical damage, theft or robbery, conservation, inventory control and delivery. It is essential that health organizations establish and monitor criteria to ensure that medicines are being received, stored and controlled effectively and correctly. Whatever the storage and distribution process, they deserve care, written procedures, defined and followed standards, and must be controlled and evaluated by performance and quality indicator